Radiation Therapy for Pelvic Malignancy and its Consequences - Ehrenpreis, Eli Daniel; Marsh, R de W.; Small Jr., William (Springer New York : Imprint: Springer, 2015)
This book provides a state-of-the-art review of the role of radiation therapy in various pelvic malignancies as well as the consequences of the radiation in the pelvic tissues. With sections covering the role of radiation therapy in the various pelvic malignancies, the pathophysiology of radiation related injury and the risk factors that increase the possibility of such an injury, and the latest in medical, endoscopic and surgical therapies for these radiation related complications the text offers a concise yet comprehensive overview of radiation therapy in the human pelvis, its role and the adverse effects on the pelvic organs. Written by experts in the field with readers in mind, Radiation Therapy for Pelvic Malignancy and its Consequences is the first of its kind standalone reference on the subject. Radiation Therapy for Pelvic Malignancy and its Consequences is of great value to urologists, medical radiation and gynecological oncologists, and gastroenterologists.